The role of N-WASP and TXNIP in skin cancer cell proliferation - Chung, Yat Joong (2019)
The ubiquitously-expressed neural Wiskott-Aldrich syndrome protein (N-WASP) regulates actin cytoskeleton remodelling. N-WASP messenger ribonucleic acid (mRNA) levels was found to be reduced in skin squamous cell carcinoma (SCC) samples compared to matched perilesional samples of 33 patients, suggesting it plays a role in skin carcinogenesis. The SCC cell line human skin squamous cell carcinoma 5 (HSC-5) was used to generate control HSC-5 (HSC-5CTR) cells HSC-5 cells overexpressing N-WASP (HSC-5N-WASP) cells. HSC-5N-WASP cells had increased epithelial cadherin (E-cadherin) and vinculin localizations but reduced cell migration, paxillin localization, cell proliferation and protein kinase B (AKT) signalling compared to HSC-5CTR cells.